2021
DOI: 10.1039/d0se01257b
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted green synthesis of levulinate esters as biofuel precursors using calix[4]arene as an organocatalyst under solvent-free conditions

Abstract: Levulinic acid, one of the top 12 value-added chemicals, can be obtained by the transformation of biomass by acid catalysis. Alkyl levulinate has been widely explored as a precursor for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…The p-sulfonic acid calix[n]arenes have been widely studied as organocatalysts for multicomponent reactions and reactions of industrial interest, such as transesterification and esterification for biodiesel production and biomass dehydration to obtain higher value-added compounds (Figure 15). [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] These calix[n]arenes are noteworthy due to the presence of sulfonic groups (SO 3 H) that act as Brønsted acids.…”
Section: P-sulfonic Acid Calix[n]arenesmentioning
confidence: 99%
See 1 more Smart Citation
“…The p-sulfonic acid calix[n]arenes have been widely studied as organocatalysts for multicomponent reactions and reactions of industrial interest, such as transesterification and esterification for biodiesel production and biomass dehydration to obtain higher value-added compounds (Figure 15). [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] These calix[n]arenes are noteworthy due to the presence of sulfonic groups (SO 3 H) that act as Brønsted acids.…”
Section: P-sulfonic Acid Calix[n]arenesmentioning
confidence: 99%
“…In addition, the authors performed the reaction using different catalyst amounts (0.75 mol%, 0.5 mol% and a catalyst‐free experiment), and observed that the reduction in the catalyst resulted in poor yields with yields of 90 %, 78 % and 30 %, respectively [45] . The best reaction conditions were set as: temperature of 80 °C (MW), 2.5 min of reaction, 1 mol% CX34 and solvent‐free conditions.…”
Section: Calix[n]arenes As Organocatalystsmentioning
confidence: 99%
“…The most highlighted LA derivatives are their esters (Adeleye et al, 2019;Castro and Fernandes, 2021;Din et al, 2019;Tiong et al, 2019). The properties of levulinate esters such as methyl and ethyl levulinate (EL) have been investigated for application as gasoline and diesel additives (Liang et al, 2020;Unlu et al, 2018;Vázquez-Castillo et al, 2019;Xu et al, 2020).…”
Section: P R E S Smentioning
confidence: 99%
“…High-efficiency process parameters is an inevitable topic of discussion in synthesis process for sustainable synthetic chemistry (Castro and Fernandes, 2021). The synthesis of levulinate ester using LA and short chain alcohol is reported to be conducted mostly via esterification reaction employing different mineral acid catalysts, such as sulphuric acid (H 2 SO 4 ), hydrochloric acid (HCl) and phosphoric acid (H 3 PO 4 ) (Bart et al, 1994;Liu et al, 2006;Pileidis et al, 2014), and various solid acids, such as sulphonic acid functionalised materials (Oliveira and Teixeira da Silva, 2014;Song et al, 2015).…”
Section: P R E S Smentioning
confidence: 99%
“…18,20 Furthermore, there is the fact that the active phase (CX4SO 3 H) has already been reported to exhibit excellent catalytic activity in numerous chemical processes. [21][22][23][24][25][26][27][28][29][30]…”
Section: Introductionmentioning
confidence: 99%